Unforgettable Moments: Ferenc Puskás and his Lasting Legacy in the Arab World: لحظات لا تنسى: فرنتس بوشكاش وإرثه الراسخ في العالم العربي - Prantner, Zoltán; Abdallah, Abdel-ati Al-naggar; István, Pál (Études sur la Région Méditerranéenne, 2024)
It is little known in Hungary that her National sporting icon Ferenc Puskás is still highly respected and admired in the Arab world. This recognition is due not only to his unparalleled footballing skills and remarkable performances with the Hungarian national team and Real Madrid, but also to his influential role as a coach in Egypt and Saudi Arabia. Throughout these activities, Puskás has consistently achieved remarkable performances within the confines of his era, which has contributed significantly to his esteemed reputation. The aim of this research is to provide a concise overview of Puskás’ career as a football star and the early stages of his coaching career. It also aims to cover the events and experiences he had during his time in Saudi Arabia and Egypt, which received considerable press coverage in the Arab media.